Two-stage free latissimus dorsi flap: A safe strategy for reconstruction of large defects of the abdominal wall. Issue 3 (June 2013) - Fejjal, Nawfal; Hafidi, Jawad; Belmir, Redouane; El Mazouz, Samir; Abbassi, Abdellah; Lahlou, Khalid; Gharib, Noureddine
Abstract We report a case of full abdominal wall reconstruction after resection of a dermatofibrosarcoma protuberans. The treatment comprised wide resection with a 5 cm peripheral margin and deep resection to a disease-free anatomical structure. The reconstruction was done in two-stages with a free latissimus dorsi flap.